Bacterial contamination on nurses' uniforms in husm medical wards: an experimental study - Cathy Wellny, Sumping (Universiti Sains Malaysia, 2008)
Several studies have demonstrated that healthcare personnel's uniforms especially nurses' uniforms could become contaminated by certain dangerous microorganisms whilst carrying out clinical duties and uniforms could be a vehicle for the transmission of infection for example Methicillin-resistant Staphylococcus aureus (MRSA), Staphylococcus aureus (S. aureus), vancomycin-resistant enterococci, and Clostridium difficile (C. difficile). These bacteria can caused several types of infection and may lead to mortality. The uniforms are also contaminated because of proper managing of the uniforms is not adhered. In this experimental cross sectional study, dominant hand's sleeve, pocket, and abdominal area of 28 nurses were swabbed at the start and end of duty and transferred to petrifilm and incubated under 35°C +/- 1°C and Escherichia coli (E. coli) and S. aureus colony count were quantified after 48 hours. The purpose of this study was to examine the degree of E. coli and S. aureus contamination present on nurses' uniforms at the start and at the end span of duty. Results demonstrated that there was a significant difference of E. coli and S. aureus contamination on nurses' uniforms at the start and at the end of duty (p=0.017, a=0.05); p=0.049, a=0.05 respectively). The resuHs also demonstrated that there is a redudion of bacterial contamination on nurses' uniforms at the end of duty. The resuHs also demonstrated that there was a significant difference of E. coli contamination on dominant hand's sleeve, pocket, and abdominal area at the start of duty. However, there was no difference of E coli contamination on dominant hand's sleeve, pocket, and abdominal area at the end of duty and S. aureus contamination between dominant hand's sleeve, pocket and abdominal area on nurses' uniform at the start and end of duty was equal. Hence, it is important for the nurses, and hospital to take action in order to minimize bacterial contamination on the uniforms to prevent transmission of infection from nurses' uniforms to patient and vice versa.